PERFORMANCE OF “PACKAGED” AND STANDARD PALM OLEIN OIL IN FRYING KERUPUK JALIN - Budiyanto Budiyanto; Meizul Zuki; Mina Sihite Hutasoit (Jurnal Agroindustri, 2012)
The objective of the study was to evaluate the changing pattern of free fatty acid (FFA) and smoke pints of packaged and standard palm olein oil in frying kerupuk jalin. The other objective was to determine the end use of both frying oils during deep fying of kerupuk jalin.  Continous deep frying with three replicates had been done for10 hours using special grade and regular frying oil without the addition of fresh oil during frying study.  The result indicated that The FFA content of both packaged and regular oils increased linearly with increasing frying time, up to 10 hours.   In addition, smoke point of the oils decreased linearly with increasing frying time.  Based on FFA of the oil, the packaged oil could last 1,4 longer than regular oil during frying of kerupuk jalin.